2017
DOI: 10.1002/mnfr.201600646
|View full text |Cite
|
Sign up to set email alerts
|

Placental dysfunction is associated with altered microRNA expression in pregnant women with low folate status

Abstract: ScopeLow maternal folate status during pregnancy increases the risk of delivering small for gestational age (SGA) infants, but the mechanistic link between maternal folate status, SGA, and placental dysfunction is unknown. microRNAs (miRNAs) are altered in pregnancy pathologies and by folate in other systems. We hypothesized that low maternal folate status causes placental dysfunction, mediated by altered miRNA expression.Methods and resultsA prospective observational study recruited pregnant adolescents and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
(72 reference statements)
0
23
0
Order By: Relevance
“…Examination of differentially expressed exosomal miRNA in PTB samples provided more distinct clusters than for normal birth. A summary of functional roles already reported for many of the miRNAs identified in exosomes from PTB suggests that miRNAs are functionally linked to cell cycle regulation (let-7a-2-5p) (38, 39), MAPK kinase kinases and inhibition of cell growth (miR-520a-3p) (40), cellular transitions and inflammation (miR-520a-3p and miR-483-3p) (41, 42), placental oxidative stress response and impairment of mitochondrial function (miR-130b-3p and miR-4433b-3p) (43, 44), macrophage programming contributing to inflammatory and oxidative stress damages (miR-142-5p) (45), preeclampsia (miR-342-3p) (46, 47), as well as placental dysfunction and impaired fetal growth due to folate deficiency (miR-222-3p) (48).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of differentially expressed exosomal miRNA in PTB samples provided more distinct clusters than for normal birth. A summary of functional roles already reported for many of the miRNAs identified in exosomes from PTB suggests that miRNAs are functionally linked to cell cycle regulation (let-7a-2-5p) (38, 39), MAPK kinase kinases and inhibition of cell growth (miR-520a-3p) (40), cellular transitions and inflammation (miR-520a-3p and miR-483-3p) (41, 42), placental oxidative stress response and impairment of mitochondrial function (miR-130b-3p and miR-4433b-3p) (43, 44), macrophage programming contributing to inflammatory and oxidative stress damages (miR-142-5p) (45), preeclampsia (miR-342-3p) (46, 47), as well as placental dysfunction and impaired fetal growth due to folate deficiency (miR-222-3p) (48).…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that folate deficiency leads to PTB [27] and SGA [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], but further studies are necessary to better investigate the potential protective role of adequate folate intake and/or folic acid supplementation. To fill this gap, the primary aim of the current study was to describe the prevalence of dietary folate intake and its determinants among pregnant women from Catania (Italy).…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al found miR-141 up-regulated in fetal growth restriction (FGR) by down-regulating its target genes [27]. Baker et al reported low maternal folate status is associated with higher incidence of small for gestation age (SGA) infants, with elevated level of miR-141-3p in placental tissues [28]. Interestingly, they also found that trophoblast proliferation was increased in low maternal folate status, to some extend that is consistent with our results i.e.…”
Section: Discussionmentioning
confidence: 99%